Diffusion weighted MRI in chronic viral hepatitis: correlation between ADC values and histopathological scores - Onur, Mehmet Ruhi; Poyraz, Ahmet Kursad; Bozdag, Pinar Gundogan; Onder, Semen; Aygun, Cem (Springer Heidelberg, 2013)
Objective To investigate the utility of apparent diffusion coefficient (ADC) measurement in the diagnosis of chronic viral hepatitis (CVH) and correlation between ADC values and histopathologic severity of CVH. Materials and methods The ADC values of liver parenchyma on diffusion-weighted magnetic resonance imaging (DWMRI) were measured in 50 patients with a history of CVH and 51 healthy subjects at b 100, b 600 and b 1,000 gradients. Comparison between mean ADC values of the CVH and control groups and correlation results between ADC values and necroinflammation and fibrosis scores in CVH were obtained. Results Mean ADC values of CVH patients were significantly lower than mean ADC values of the control group at b 100 and b 600 gradients (P< 0.05). There was no significant difference between the CVH and control groups at the b 1,000 gradient (P> 0.05). No significant correlation was found between ADC values and histopathologic scores of CVH (P> 0.05). Conclusion ADC values obtained at the b 100 and b 600 gradients can be used to distinguish between the liver parenchyma of CVH and healthy subjects. ADC measurement was not found to be useful for estimation of the degree of necroinflammation and fibrosis in CVH. Teaching Points In chronic viral hepatitis apparent coefficient values are decreased in the liver There is no correlation between ADC values and histopathologic severity of CVH DW images obtained at low b values have more ability to demonstrate an ADC decrease in viral hepatitis
Keywords: Chronic viral hepatitis; Fibrosis; Diffusion weighted MRI; ADC measurements